A Chinese Herbal Preparation Containing Radix Salviae Miltiorrhizae, Radix Notoginseng and Borneolum Syntheticum Reduces Circulating Adhesion Molecules. (23rd June 2011) - O'Brien, Kylie A.; Ling, Shanhong; Abbas, Estelle; Dai, Aozhi; Zhang, Jiansheng; Wang, Wen Cheng; Bensoussan, Alan; Luo, Ruizhi; Guo, Zhi-Xin; Komesaroff, Paul A.
Abstract : Circulating adhesion molecules (CAMs), surface proteins expressed in the vascular endothelium, have emerged as risk factors for cardiovascular disease (CVD). CAMs are involved in intercellular communication that are believed to play a role in atherosclerosis. A Chinese medicine, the "Dantonic Pill" (DP) (also known as the "Cardiotonic Pill"), containing three Chinese herbal material medica, Radix Salviae Miltiorrhizae, Radix Notoginseng and Borneolum Syntheticum, has been used in China for the prevention and management of CVD. Previous laboratory and animal studies have suggested that this preparation reduces both atherogenesis and adhesion molecule expression. A parallel double blind randomized placebo-controlled study was conducted to assess the effects of the DP on three species of CAM (intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 and endothelial cell selectin (E-selectin)) in participants with mild-moderate hypercholesterolemia. Secondary endpoints included biochemical and hematological variables and clinical effects. Forty participants were randomized to either treatment or control for 12 weeks. Treatment with DP was associated with a statistically significant decrease in ICAM-1 (9% decrease, P = .03) and E-Selectin (15% decrease, P = .004). There was no significant change in renal function tests, liver function tests, glucose, lipids or C-reactive protein levels and clinical adverse effects did not differ between the active and the control groups. There were no relevant changes in participants receiving placebo. These results suggest that this herbal medicine may contribute to the development of a novel approach to cardiovascular risk reduction.